Interpenetrating network of alginate-human adipose extracellular matrix hydrogel for islet cells encapsulation - Wang, Jun Kit (2022)
Transplantation of microencapsulated islet cells holds great potential for the treatment of type 1 diabetes mellitus. However, its clinical translation is hampered by the peri-transplantation loss of islet viability and functionality in the microcapsules. In this work, a novel islet cells biomimetic microencapsulant material that is based on the interpenetrating networks of alginate and extracellular matrix (ECM) hydrogel composite (AEC) is presented. The ECM component is derived from human lipoaspirate. In situ encapsulation of pancreatic β islet cells (MIN6 β-cells) can be achieved via ionotropic gelation of the alginate matrix and thermal-induced gelation of the pepsin-solubilized ECM pre-gel. Due to the enhanced cell-matrix interaction, islets encapsulated within the AEC microcapsules (≈640 µm) display sevenfold increase in cell growth over 1 week of culture and characteristic glucose-stimulated insulin response in vitro. The results show that the AEC microcapsule is a potent platform to bioaugment the performance of islet cells.